2006
DOI: 10.1124/dmd.106.013243
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the HumanUGT1Locus in Transgenic Mice by 4-Chloro-6-(2,3-xylidino)-2-pyrimidinylthioacetic Acid (WY-14643) and Implications on Drug Metabolism through Peroxisome Proliferator-Activated Receptor α Activation

Abstract: The UDP-glucuronosyltransferase (UGT) 1A genes in humans have been shown to be differentially regulated in a tissue-specific fashion. Transgenic mice carrying the human UGT1 locus (Tg-UGT1) were recently created, demonstrating that expression of the nine UGT1A genes closely resembles the patterns of expression observed in human tissues. In the present study, UGT1A1, UGT1A3, UGT1A4, and UGT1A6 have been identified as targets of the peroxisome proliferator-activated receptor (PPAR) alpha in human hepatocytes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 29 publications
5
82
0
Order By: Relevance
“…If tumor Ugt1a gene expression is impaired, induction of gene activity in nondiseased normal tissue may protect the surrounding epithelial cells from SN-38 damage by increasing glucuronidation capacity and improving drug tolerance. For example, UGT1A1, the primary UGT involved in SN-38 glucuronidation (15), can be regulated by induction of the human UGT1A1 gene after activation of XNRs PXR (39,40), CAR (15), and PPARα (41). One could envision that potential therapeutics could be developed to target induction of the UGT1A1 gene in healthy tissue, thus providing an added level of protection toward the toxicity inherent in the accumulation of SN-38.…”
Section: Discussionmentioning
confidence: 99%
“…If tumor Ugt1a gene expression is impaired, induction of gene activity in nondiseased normal tissue may protect the surrounding epithelial cells from SN-38 damage by increasing glucuronidation capacity and improving drug tolerance. For example, UGT1A1, the primary UGT involved in SN-38 glucuronidation (15), can be regulated by induction of the human UGT1A1 gene after activation of XNRs PXR (39,40), CAR (15), and PPARα (41). One could envision that potential therapeutics could be developed to target induction of the UGT1A1 gene in healthy tissue, thus providing an added level of protection toward the toxicity inherent in the accumulation of SN-38.…”
Section: Discussionmentioning
confidence: 99%
“…CYP4 family members were the first fibrate-induced XME target genes shown to be involved in omega-hydroxylation of fatty acids [5]. PPARα is involved in regulation of all phases of the XME system including regulation of many UGTs (UGT1A1, 1A3, 1A4 [51], 1A9 [52], 2B4 [53]). PPARα-induced hepatic UGTs are possibly involved in detoxification of eicosanoids, as discussed in section 4.4.…”
Section: Pparαmentioning
confidence: 99%
“…It is tempting to speculate that evolution of the gtPBREM cluster of binding sites for a number of LATFs in the promoter of UGT1A1 [46,47] may be related to the need for perinatal UGT1A1 induction in primates. This cluster contains binding sites for CAR and PXR [47], AhR [33], Nrf2 [76], PPARα [51] and for the glucocorticoid receptor [47]. It is obvious that perinatal induction represents a stressful condition.…”
Section: Page 9 Of 31mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is clear that the alternative usage of duplicated first exons is the basis of UGT1A function and expression diversities. Besides, all this tissue-specific expression is well orchestrated by the cooperative interaction between transcription factors and the transcription initiation complex (for review see (Mackenzie et al, 2003;Owens, Basu, & Banerjee, 2005;Strassburg, Kalthoff, & Ehmer, 2008;Tukey & Strassburg, 2001) (Gardner-Stephen & Mackenzie, 2008) Studies concerning UGT1A promoter-interacting factors have revealed the binding of some important activators, such as HNF-1, cdx2, Nrf2, PXR, XRE (AhR) and CAR (Aueviriyavit, Furihata, Morimoto, Kobayashi, & Chiba, 2007;Bonzo, Belanger, & Tukey, 2007;Buckley & Klaassen, 2009;Gregory, Lewinsky, Gardner-Stephen, & Mackenzie, 2004;Senekeo-Effenberger et al, 2007;Sugatani, Sueyoshi, Negishi, & Miwa, 2005;Verreault et al, 2006;Yuan, Li, & Yang, 2007). Transcriptional regulation of the UGT1A gene by transcription factors is more specifically addressed in some following chapters.…”
Section: The Human Ugt1a Family Membersmentioning
confidence: 99%